PENGARUH MEDIA PESTA BERBASIS QR CODE TERHADAP KEMAMPUAN LITERASI SAINS SISWA SEKOLAH DASAR - Akmal Al-Fikri, Haidar; Ayu Febrianti, Fitri; Sukma Nugraha, Widdy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low scientific literacy skills of elementary school students, characterized by low conceptual understanding and minimal use of technology in learning, encourages the need for more interactive learning media innovations. This study aims to determine the effect of PESTA (Petualangan Alam Semesta) media, a learning media based on snakes and ladders games integrated with QR Code, on the scientific literacy skills of fifth-grade students of SDN 2 Pakuwon on the solar system material. The study used a quantitative method with a quasi-experimental approach through a pretest-posttest control group design. The research sample consisted of 39 students divided into an experimental class (19 students) and a control class (20 students), selected using a purposive sampling technique. Data were collected through a scientific literacy ability test in the form of multiple-choice and essay questions, then analyzed using the Mann-Whitney U Test, N-Gain, and Independent Sample t-Test. The results showed that the average posttest score of the experimental class increased from 64.84 to 87.80, while the control class from 68.45 to 85.46. The average N-Gain of the experimental class (0.696) was higher than that of the control class (0.541), and the results of the hypothesis test showed a significance value of 0.018 (<0.05). Thus, PESTA media has a significant effect on improving students' scientific literacy skills and has implications as an alternative innovative learning media that supports technology-based science learning in elementary schools